Tanzania Mainland Poverty Assessment - World Bank Group (World Bank, Washington, DC, 2015)
Since the early 2000s, Tanzania has seen remarkable economic growth and strong resilience to external shocks. Yet these achievements were overshadowed by the slow response of poverty to the growing economy. Until 2007, the poverty rate in Tanzania remained stagnant at around 34 percent despite a robust growth at an annualized rate of approximately 7 percent. This apparent disconnect between growth and poverty reduction has raised concerns among policy makers and researchers, leading to a consensus that this mismatch needed to be addressed with a sense of urgency. Over the past few years, the National Strategy for Growth and Reduction of Poverty (MKUKUTA) in Tanzania has given high priority to eradicating extreme poverty and promoting broad-based growth. Achieving pro-poor growth has also been widely recognized by the World Bank as a critical strategy for accelerating progress toward its twin goals of eliminating extreme poverty at the global level by 2030 and boosting shared prosperity by fostering income growth among the bottom 40 percent in every country. The official poverty figures announced by the government in November 2013 have revealed that the national strategy against poverty has begun to facilitate reductions. The basic needs poverty rate has declined from around 34 percent to 28.2 percent between 2007 and 2012, the first significant decline in the last 20 years. Identifying the policy mechanisms that have helped to increase the participation of the poor in the growth process and to speed pro-poor growth is therefore important for present and future decision-making in Tanzania on how best to eradicate poverty. Such task requires a rigorous analysis of the evolution of poverty and of the linkages between poverty, inequality, and economic growth. This report uses the availability of the new Tanzanian Household Budget Survey (HBS) for 2011 and 2012, as well as the new rebased GDP figures released in December 2014, as an opportunity to address these issues. More specifically, the report examines the recent trends in poverty and inequality and their determinants and explores how responsive poverty reduction was to economic growth and the obstacles to achieving it.